2011
DOI: 10.1007/s13197-011-0427-8
|View full text |Cite
|
Sign up to set email alerts
|

Effect of drying temperature and slice size on quality of dried okra (Abelmoschus esculentus (L.) Moench)

Abstract: Okra (Abelmoschus esculentus (L) Moench) is an important vegetable crop of India. Dried okra pods have wide use in snacks and are in great demand for domestic as well as export market. Hence, effect of four slice sizes (1, 2, 3 and 4 cm) and four drying temperatures (50, 60, 70 and 80°C) on quality of hot air dried okra were studied. Okra pods were dried in the form of slices cut across the length at different temperatures. Quality assessment of okra was done on the basis of protein, ascorbic acid and fibre co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
28
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(35 citation statements)
references
References 16 publications
4
28
1
Order By: Relevance
“…Similar findings were also reported by several authors for various foods using microwave drying (Maskan 2000;Soysal 2004). The drying times obtained in this study were much shorter (4-7 min) as compared to the results reported by Pendre et al (2012) using a convective hot air dryer for drying okra. The appearance of okra at different levels and time intervals is shown in Fig.…”
Section: Results and Discussion Drying Characteristics Of Okracontrasting
confidence: 55%
See 1 more Smart Citation
“…Similar findings were also reported by several authors for various foods using microwave drying (Maskan 2000;Soysal 2004). The drying times obtained in this study were much shorter (4-7 min) as compared to the results reported by Pendre et al (2012) using a convective hot air dryer for drying okra. The appearance of okra at different levels and time intervals is shown in Fig.…”
Section: Results and Discussion Drying Characteristics Of Okracontrasting
confidence: 55%
“…Because of its sensitivity to storage, most fresh okras are preserved in some way. Okra is a good source of carbohydrate, protein, dietary fiber, calcium, magnesium, potassium, and vitamins A and C (Pendre et al 2012). Vegetables are highly perishable because of their high metabolic activity.…”
Section: Introductionmentioning
confidence: 99%
“…As the ascorbic acid is highly sensitive towards the temperature and rapidly degrade in the presence of heat, the samples with more thickness and dried with lower temperature, retain maximum ascorbic acid. Similar results are reported by Ramallo and Mascheroni [10] during drying of pineapple half slices, Marfil et al [11] for tomatoes and Pendre et al [12] in case of okra drying.…”
Section: Effects Of Different Temperature and Thickness Levels On Ascsupporting
confidence: 89%
“…Accordingly, they exhibit relatively high metabolic activity compared with other plantderived foods such as seeds. This metabolic activity continues after harvesting, thus making most fruits highly perishable commodities (Atungulu et al, 2004;Pendre et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Accordingly, they exhibit relatively high metabolic activity compared with other plantderived foods such as seeds. This metabolic activity continues after harvesting, thus making most fruits highly perishable commodities (Atungulu et al, 2004;Pendre et al, 2012).Drying improves the product shelf life without addition of any chemical preservative and reduces both the size of package and the transport cost (Al-Harahsheh et al, 2009;Figiel, 2010;Singh et al, 2010). Drying also assists in reducing post harvest losses of fruits and vegetables especially, which can be as high as 70% (Tunde-Akintunde and Ogunlakin, 2013).…”
mentioning
confidence: 99%